Effects of Direct Air Capture Technology Availability on Stranded Assets and Committed Emissions in the Power Sector - Pradhan, Shreekar; Shobe, William M.; Fuhrman, Jay; McJeon, Haewon; Binsted, Matthew; Doney, Scott C.; Clarens, Andres F. (Frontiers in Climate, 2021)
We examine the effects of negative emission technologies availability on fossil fuel-based electricity generating assets under deep decarbonization trajectories. Our study focuses on potential premature retirements (stranding) and committed emissions of existing power plants globally and the effects of deploying direct air carbon capture and biomass-based carbon capture and sequestration technologies. We use the Global Change Analysis Model (GCAM), an integrated assessment model, to simulate the global supply of electricity under a climate mitigation scenario that limits global warming to 1.5°-2°C temperature increase over the century. Our results show that the availability of direct air capture (DAC) technologies reduces the stranding of existing coal and gas based conventional power plants and delays any stranding further into the future. DAC deployment under the climate mitigation goal of limiting the end-of-century warming to 1.5°-2°C would reduce the stranding of power generation from 250-350 GW peaking during 2035-2040 to 130-150 GW in years 2050-2060. With the availability of direct air capture and carbon storage technologies, the carbon budget to meet the climate goal of limiting end-of-century warming to 1.5°-2°C would require abating 28-33% of 564 Gt CO2 -the total committed CO2 emissions from the existing power plants versus a 46-57% reduction in the scenario without direct air capture and carbon storage technologies.